Impact Assessment of Implementing Several Retrofitting Strategies on the Air-Conditioning Energy Demand of an Existing University Office Building in Santiago, Chile - Vasco-Calle, D; Venegas-Troncoso, T (Multidisciplinary Digital Publishing Institute (MDPI), 2023)
This work analyzed the thermal behavior of an existing building, considering different retrofitting strategies. The methodology starts with an in-situ survey that allowed for obtaining information about occupation, work schedules, envelope materials, lighting, and equipment, which was vital to develop an energy model of the building. Then, the thermal analysis, employing simulations, demonstrates a higher relevance of heat flows through the building’s envelope than internal loads and higher cooling rather than heating demands. Afterward, several retrofit strategies focusing on modifying architectural elements were assessed. Finally, these strategies were compared based on their impact on the air-conditioning energy demand. A systematic review identified a lack of studies relating certification and energy policies to buildings retrofitting. Therefore, we assessed the energy performance of the building, when modified to meet the baseline requirements set on the Chilean certification requirements for sustainable buildings, to verify if the certification is a suitable method to assess the energy efficiency of an office building. Although the study only involves a single building, it aims to illustrate identified limitations using the energy policies for Chilean public buildings. The Chilean certification for sustainable buildings seems not to be suitable for the evaluation of energy consumption for the retrofit of existing buildings. Although this study does not demonstrate general trends, it presents a precedent for subsequent studies to evaluate the relevance of the Chilean certification guidelines. © 2023 by the authors.